2022
DOI: 10.3389/fneur.2022.964761
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of menstrual disorders and reproductive hormones in women with epilepsy at an Indonesian national referral hospital

Abstract: ObjectiveMenstrual disorders are more common in women with epilepsy than in those without epilepsy. This study aimed to examine the characteristics of reproductive function in women with epilepsy at an Indonesian national referral hospital.MethodsA case-control study was conducted from March 2020 to March 2021. Women with and without epilepsy aged ≥18 years were enrolled. All women were premenopausal before epilepsy diagnosis. Data on demographic characteristics, menstrual profiles, epileptic syndrome, seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Another study conducted by Octaviana et al examined hormonal levels in 100 women with irregular menstrual cycles. They measured estrogen, progesterone, and follicle-stimulating hormone levels and identified notable distinctions in these hormone levels among women with varying menstrual patterns (10). The present study validated that the consumption of smokeless tobacco in rats led to myometrial degeneration along with fibrosis and edema.…”
Section: Discussionsupporting
confidence: 74%
“…Another study conducted by Octaviana et al examined hormonal levels in 100 women with irregular menstrual cycles. They measured estrogen, progesterone, and follicle-stimulating hormone levels and identified notable distinctions in these hormone levels among women with varying menstrual patterns (10). The present study validated that the consumption of smokeless tobacco in rats led to myometrial degeneration along with fibrosis and edema.…”
Section: Discussionsupporting
confidence: 74%
“…Dysmenorrhea is more prevalent among women with epilepsy (Serret-Montoya et al, 2014). A case-control study with 66 participants similarly confirmed this result (Octaviana et al, 2022). However, the direction and mechanism of the correlation between dysmenorrhea and epilepsy are unclear.…”
mentioning
confidence: 57%
“…The global lifetime prevalence of epilepsy is estimated to be about 7.6 cases per 1000 people (Olusanya et al, 2020). Understanding the epidemiology of epilepsy is critical to developing healthcare policy, implementing prevention strategies, and understanding the health resource needs of these challenging patient populations (S. Wang et al, 2023).Current observational studies suggest a correlation between dysmenorrhea and epilepsy (Ingudomnukul et al, 2007;Octaviana et al, 2022;Pohl et al, 2014). Dysmenorrhea is more prevalent among women with epilepsy (Serret-Montoya et al, 2014).…”
mentioning
confidence: 99%